Medley Global Advisors : could the information service survive without its founder? - Rae, Douglas W., (SAGE knowledge. Cases., 2016)
Richard Medley is not by nature a patient man, and the dinner in a trendy lower Manhattan restaurant seemed interminable to him. The Swiss banking official to his right ignored Medley through drinks, appetizers, even a long first course. Eventually losing interest in the conversational thread that had kept him busy heretofore, the gentleman turned abruptly to Medley, asking without benefit of an inquiry about names, "And what do you do?" Amused by the question, Richard Medley explained that he was in the business of business intelligence - selling information about the probable actions of governments across the globe as they might impact top management of major corporations.